Response strategies used to mitigate the effect of extreme weather on rural and remote housing in Australia. Issue 1 (January 2022) - Jensen, Christopher A.; Yule, Jessamie
Abstract: In the extreme climates of Australia, rural and remote locations have special site and dwelling requirements and therefore special design solutions. This can include construction constraints, bushfire risk, resource efficiency, comfort and respect for the surrounding environment and heritage. Existing regulations targeted at extreme weather impacts such as bushfire, flood, cyclones, and heatwaves often impact the design and material choices for rural and remote housing due to their exposed locations, including housing proposed for rebuild following damage resulting from an extreme weather event. These regulations also lead to increased costs and uncertainty about the suitability of rural land for construction, making it challenging for rebuilding communities in affected areas. Such well-intentioned regulations also create limitations on innovation through experimental / bespoke building design, such as; 1) novel solutions to extreme weather mitigation and resistance 2) material choices for construction; and 3) achievement of operational and embodied energy reductions. Experimental buildings provide significant innovation benefits to industry as is often seen in the development of sustainable and high-performance buildings. This research examines the academic and industry knowledge of current design regulations for extreme weather events and implications for experimental and innovative design, highlighting the challenges for buildings to achieve increasing standards of environmental performance whilst ensuring resilience in the face of increasing extreme weather events, with a specific focus on rural communities. Case study analysis is used to provide an understanding of the focus and strategies used by different groups in different locations to address the impacts of extreme weather.